Effectiveness of and factors associated with clinical response to methotrexate under daily life conditions in Asian patients with psoriasis: A retrospective cohort study - Kamolwan Pongparit (2019)
© 2018 Japanese Dermatological Association Given the relative scarcity of data concerning the efficacy of methotrexate under daily life conditions in psoriasis, this study aimed to investigate the effectiveness of methotrexate in Asian psoriatic patients and to identify factors associated with clinical response. This observational retrospective cohort study included adult psoriatic patients who had been treated with or were going to start methotrexate. Psoriasis Area and Severity Index (PASI) scores at baseline and at 3, 6 and 12 months were recorded. At 3 months, patients achieving 50% or more reduction from baseline PASI score were defined as responders. One hundred, 74 and 61 patients were followed for 3, 6 and 12 months, respectively. Mean follow-up time was 15.3 ± 10.2 months. A reduction in PASI score of at least 75% was achieved in 26%, 32.5% and 45.2% at 3, 6 and 12 months, respectively. At 12 and 24 months, Kaplan–Meier analysis showed 68.7% and 52.1% probability of drug survival, respectively. Male sex, body mass index (BMI) of less than 25 kg/m 2 and absence of abdominal obesity were factors associated with response to treatment in univariate analysis. Male sex was the only significant factor in multivariate analysis. The effectiveness of methotrexate in clinical practise seemed to be lower than in clinical trials, but effectiveness increased with longer duration of treatment. Problems associated with methotrexate use in clinical practise may be due to medication adherence rather than lack of medication effectiveness. Female sex, abdominal obesity and BMI of 25 kg/m 2 or more might decrease response to methotrexate.